EU – China food trade perspectives - Anton Kostadinov (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
China's striving to ensure food security for its large population, and that problem I well known. In about one fifth of global population is living in China, in the same time should relay only 1/15 from rural land and 8% of fresh water. China's population grows not only as a numbers, but also it is urbanizing in a large scale, the disposable incomes are also growing. It all means that food consuming pattern in China is also changing, and food consumption in the country will grow in both dimension - as a quantity and as a quality. EU - China trade relations are complicated and protectionism could be seen in both sides. EU have large trade deficits with China. The most member states have also large deficits, but not Germany and Finland. EU member states have very different positions about trade relations with China. In the food sector EU experiences overproduction, closed markets in Russian Federation, and internal market tensions. Furthermore, EU has placed a strong emphasis on speeding up Free trade agreements with so dynamic Asian countries, including China, but there are no plausible results yet.
Keywords: F15; F42; 330; China; EU food trade; food security